[PS 01-18] MECHANISM OF HYPERTENSIVE CARDIAC HYPERTROPHY IN CULTURED NEONATAL RAT VENTRICULAR CARDIAC MYOCYTES. (September 2016) - Sun, Gang; Yu, Hui; Wang, Zhanli; Yang, Xiaomin; Yue, Jianwei; Qu, Shuangli
Abstract : Objective: hypertrophy and impaired cardiac function are commonly observed in some patients with hypertension. Angiotensin II is a critical growth factor to mediate cardiac hypertrophy. MicroRNAs (miRs) have been identified and associated with several cardiovascular diseases, including ischemic cardiomyopathy and cardiac hypertrophy. MiR-21 was reported to be upregulated during adult rat cardiac remodeling. The importance of miR-21* in cardiomyocyte hypertrophy has also been demonstrated. Design and Method: Wistar rats (weight, 120–150 g) were purchased. Ventricular cardiomyocytes were isolated from 1 to 2-day-old neonatal wistar rat as described previously with minor modification. After 24 h of serum starvation, the cardiomyocytes were stimulated with or without 1 umol/L Ang II for 48 h. The hypertrophy cardiomyocytes were identified by semi-quantitative RT-PCR assay. Total miRNAs were extracted using mirVANA miRNA isolation kit. The miRNAs quality and quantity were determined by a NanoDrop 1000 Spectrophotometer. The miRNAs were reverse transcribed by TaqMan MicroRNA Reverse Transcription Kit. qRT-PCR was performed using TaqMan Universal PCR Master Mix II on the ABI 7500 System according to the manufacturer's recommendations. Total proteins isolated from cultured cardiomyocytes, with or without 1 umlo/L Ang II for 48 h, were prepared by M-PER mammalian protein extraction reagent. SDS-polyacrylamide gel electrophoresis was performed using standard procedures. Results: We demonstrated that miR-21* was markedly upregualted in Ang II-induced neonatal rat cardiac myocytes, while miR-21 was reduced. We might speculate that the miRNA expression profile is different between neonatal rat and adult rat cardiac myocytes. Our results further showed that Ang II led to a significant reduction of PTEN expression level and a significant promotion of phosphorylation level of PI3K. In contrast, treatment with prohypertrophic molecule Ang II reduced the phosphorylation level of Akt. Conclusions: We therefore speculate that miR-21* might have two opposite effects on Ang II-induced cardiac hypertrophy through various signaling pathways.